2007
DOI: 10.1007/s10832-007-9322-0
|View full text |Cite
|
Sign up to set email alerts
|

Microwave dielectric properties of Mg4Nb2O9 ceramics produced by hydrothermal synthesis

Abstract: Mg 4 Nb 2 O 9 ceramics have been prepared by a hydrothermal synthesis in order to reduce the sintering temperature. The sintering and microwave dielectric properties of the hydrothermally processed Mg 4 Nb 2 O 9 were studied under various sintering temperatures ranging from 900 to 1300°C. The highest Q×f o value of 26,069 GHz was obtained at the sintering temperature of 1300°C and is attributed to the increased density and appropriate grain growth. t f value of −17.1 ppm/°C was improved by the addition of TiO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…A minor phase of Mg 5 Nb 4 O 15 with orthorhombic symmetry was developed accompanying Mg 4 Nb 2 O 9 as separated phases just at 30.16 • and 31.30 • .As the temperature increasing to 850 • C, the intensity of the Mg 4 Nb 2 O 9 peaks was gradually enhanced and the Mg 5 Nb 4 O 15 phase had been found to nearly disappear. Using the sol-gel method, we found that the calcination temperature was remarkably decreased to 550 • C, in comparison to these of the conventional mixed oxide route reported earlier [2][3][4]7,8] and other chemical methods [9][10][11][12][13] as shown in Table 1.…”
Section: Methodsmentioning
confidence: 55%
See 2 more Smart Citations
“…A minor phase of Mg 5 Nb 4 O 15 with orthorhombic symmetry was developed accompanying Mg 4 Nb 2 O 9 as separated phases just at 30.16 • and 31.30 • .As the temperature increasing to 850 • C, the intensity of the Mg 4 Nb 2 O 9 peaks was gradually enhanced and the Mg 5 Nb 4 O 15 phase had been found to nearly disappear. Using the sol-gel method, we found that the calcination temperature was remarkably decreased to 550 • C, in comparison to these of the conventional mixed oxide route reported earlier [2][3][4]7,8] and other chemical methods [9][10][11][12][13] as shown in Table 1.…”
Section: Methodsmentioning
confidence: 55%
“…And now there have been many investigations of the chemical processing methods [9][10][11][12][13], which have been developed as alternatives to the conventional solid state reaction of mixed oxides for producing ceramics to reduce the sintering temperature. For example, the MN ceramic was successfully fabricated at 950 • C for 2 h in air by the precipitation process with ε r = 8.5, Qf = 5500 GHz [9] and by a hydrothermal method the MN ceramic was obtained with the highest Qf value of 26,069 GHz at 1300 • C [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several dielectric ceramics with low K and high Qf value, such as Al 2 O 3 [2], Mg 4 Nb 2 O 9 [3], Ca 3 Sn 2 SiO 9 [4], Mg 2 SiO 4 [5], and Zn 2 SiO 4 [6] have received attention with respect to applications as ceramic substrate materials of microwave integrated circuits (MIC) to minimize the cross-coupling with conductors and to shorten the time for electronic signal transmission.…”
Section: Introductionmentioning
confidence: 99%
“…coprecipitation, hydrothermal and sol-gel [1][2][3]. The Mg 4 Nb 2 O 9 (MN) ceramic by the conventional solid-state method possesses ε r =12.4, τ f =À 70 ppm/1C and a high Q Â f=193,000 GHz [4].…”
Section: Introductionmentioning
confidence: 99%